Falsafah dan konsep Sastera Islam mengikut Sidek Baba = The philosophy and the concept of Islamic Literature according to Sidek Baba - Yaacob, Adli; Mohd Fadzil, Farah Syafiqah (Global Academic Excellence (M) Sdn Bhd (GAE), 2022)
Professor Datuk Dr. Sidek Baba is an intellectual and authoritative scientist. He has produced papers on Islamic literature and Islamic writings while pursuing studies at the Diploma in Islamic Studies at Universiti Kebangsaan Malaysia in 1985. In his study, he emphasized the concept of Islamic literature and Islamic writing by bringing the differences in the use of both. The study that Sidek Baba has done is very closely related to the title of this study, which is about debating the concept of Islamic literature in Sidek Baba's views and comments. This study explains the origins of manners and Islamic writings and how the history of Islamic literary ideas in the Arab world and Malay land has emerged. Furthermore, this study is further reinforced by how Sidek Baba accepts the work and art of Muslims and non-Muslims by submitting their concrete arguments and opinions about the conditions of accepting and practicing the content of a work because for him the world of writing works is a daunting field unintelligible for a writer, for the writer who is always practicing with the Islamic teaching to produce a moral Islam that thereby elevates the rank and value of Islam to all over the world.